2017
DOI: 10.1016/j.jfma.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease attributable to ambient fine particulate matter exposure in Taiwan

Abstract: Ambient PM pollution is a major mortality risk factor in Taiwan. Aggressive and multisectorial intervention strategies are urgently needed to bring down the impact of air pollution on environment and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…b e end year in one-year survival is 2014, the end year in three-year survival is 2012, and the end year in five-year survival is 2010. deteriorating air pollution in the Asian countries after decades of rapid industrialization and urbanization has been recognized as the worst region among the world [30]. e potential health impacts of air pollution are multisystemic, and several studies had established the causal link of PM2.5 with lung cancer, ischemic heart disease, stroke, and pulmonary diseases [31]. Taiwan has established a nationwide air quality monitoring system and has been releasing a monthly report of PM2.5 concentration since 2005 [21].…”
Section: Discussionmentioning
confidence: 99%
“…b e end year in one-year survival is 2014, the end year in three-year survival is 2012, and the end year in five-year survival is 2010. deteriorating air pollution in the Asian countries after decades of rapid industrialization and urbanization has been recognized as the worst region among the world [30]. e potential health impacts of air pollution are multisystemic, and several studies had established the causal link of PM2.5 with lung cancer, ischemic heart disease, stroke, and pulmonary diseases [31]. Taiwan has established a nationwide air quality monitoring system and has been releasing a monthly report of PM2.5 concentration since 2005 [21].…”
Section: Discussionmentioning
confidence: 99%
“…We obtained data on particles measuring less than 2.5 μm in diameter (PM 2.5 ) from Taiwan Air Quality Monitoring Network established by the Taiwan Environmental Protection Administration (EPA) [17]. …”
Section: Methodsmentioning
confidence: 99%
“…PM 2.5 is a complex mixture of extremely small particles and liquid droplets that include various components including acids, organic chemicals (such as polycyclic aromatic hydrocarbons (PAHs), nitro-and oxygenated-PAHs), heavy metals, and soil or dust particles (Yue et al, 2015), which can directly affect the acidity of precipitation, degrade atmospheric visibility, and make the numerous harmful effects on individuals, even increased mortality or morbidity (Zhang et al, 2012(Zhang et al, , 2016Eze et al, 2014). Epidemiological studies have indicated that PM 2.5 is not only linked to an increased risk of hospitalization and mortality from cardiopulmonary diseases (Lo et al, 2016;Gillespie et al, 2013), but also associated with the development and progression of neurodegenerative disorders, such as Alzheimer's and Parkinson's diseases (Genc et al, 2012).…”
Section: Introductionmentioning
confidence: 99%